A solution to the economic dispatch problem for AC-DC systems - Nerves, Allan C.
A method is presented for solving the economic dispatch problem for AC-DC systems. Equations are formulated to derive penalty factors for these systems. The solution utilizes a simultaneous-method Newton Raphson load flow within its overall procedure. A direct exact calculation of the penalty factors from the Jacobian of the converged load flow is proposed. These penalty factors are used to satisfy the incremental cost criterion for economic dispatching. Tests and results are given for a hypothetical system.